2013
DOI: 10.3109/00498254.2013.851431
|View full text |Cite
|
Sign up to set email alerts
|

Species difference in the inhibitory potentials of non-steroidal anti-inflammatory drugs on the hepatic sulfation and glucuronidation of bioactive flavonoids: differential observations among common inhibition parameters

Abstract: 1. This study elucidated the species differences between rats and humans in the inhibitory potential of drugs against sulfation and glucuronidation, and whether such differences depend on the inhibition parameter adopted. 2. With 14 non-steroidal anti-inflammatory drugs (NSAIDs) as model inhibitors and three flavanoids baicalein, wogonin and oroxylin A as model substrates, three common inhibition parameters percentage of control, IC50 and Ki were determined in rat liver cytosols (RLCs), human liver cytosols (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…A GMFE of 1 represents perfect predictability, while GMFE values between 0.5 and 2 indicate that most of the predicted AUC p.o. fall within the 2‐fold range of the observed values .…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…A GMFE of 1 represents perfect predictability, while GMFE values between 0.5 and 2 indicate that most of the predicted AUC p.o. fall within the 2‐fold range of the observed values .…”
Section: Methodssupporting
confidence: 78%
“…The bias (deviation from unity) of the different prediction approaches was assessed by determining the calculated geometric mean fold error (GMFE) using the following equation : GMFE=0.25em10mean()logpredictedDDIobservedDDI…”
Section: Methodsmentioning
confidence: 99%
“…From our in vitro metabolism inhibition study using rat liver microsomes, SR extract dose-dependently inhibited the hydroxylation and glucuronidation of MEF, with IC 50 values of 60 mg/ml and 100 mg/ml, respectively (data not shown). Meanwhile, MEF competitively inhibited the glucuronidation of baicalein, wogonin, and oroxylin in rat liver microsomes with K i values of 71-743 mM (Fong and Zuo, 2014). These mechanistic studies suggested MEF and SR components might interact via metabolism inhibitions.…”
Section: Minimal Pharmacokinetic Interactions Between Sr and Mefmentioning
confidence: 88%
“…These similarities may increase the opportunity of co-administration by patients and, at the same time, the potential of pharmacokinetic and/or pharmacodynamic interactions. From our previous in vitro screening results among 14 NSAIDs, mefenamic acid (MEF) was the most potent inhibitor on the hepatic glucuronidation and sulfation of three major components of SR, the flavonoids baicalein, wogonin, and oroxylin A, with inhibition constants K i ranging from 5 to 195 μM (Fong and Zuo, 2014). Therefore, MEF was selected in the current study for further in vivo evaluations of its potential interaction with SR extract.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of these regioselectivities in glucuronidation of flavonoids, UGT1A8 and UGT1A9 seem to be the dominant isoforms involved in the glucuronidation of wogonin and oroxylin A, whereas UGT1A1 and UGT1A9 are involved in the glucuronidation of baicalein [163].…”
Section: Metabolism and Stability To Metabolic Attackmentioning
confidence: 99%